Kemajuan Aliran Pencak Silat Tradisional Bakti Jang Pat Petulai Daerah Tunggang Ulau Dues - Helvi Darsi; Muhammad Supriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aimed to examine Traditional Bakti martial arts flow. This type of research was qualitative, the data were taken through observation and interviews using snowball techniques through key informant namely Tua Silat Bakti, other informants were expanded from that informant so that all the data needed was completed, then the data was analyzed by using words which could be arranged in expanded text or did an analysis of data taken from the field and then it was described in narrative form. The results of this study, traditional bakti martial art came from the word filial*(berbakti)* which first developed by the ancestors, this martial art was developed rapidly in 1965 to 1990, and the Tunggang community began learning less the Traditional Bakti jat Pat Petulai Pencak Silat since 1987. In conclusion, the main form of the martial art movement would be seen in the speed and attack accuracy and sword attack (sword), dodgery and piseu attack(knife), as well as accuracy and attack with empty hand. Keywords: Traditional Pencak Silat, Jang Pat Petulai